2021
DOI: 10.4103/njcp.njcp_373_19
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Enhances Functions and Quality of Life in Older Patients with Breast Cancer-Related Lymphedema

Abstract: Background: Lymphedema of the arm is one of the most common complications following breast cancer surgery. Aims: The primary aim of this study was to evaluate the effects of complex decongestive physical therapy (CDPt) on upper extremity functions, activities of daily living (ADL), and quality of life (QoL), and secondly the effects of the degree of lymphedema on post-treatment differences in older patients with breast cancer-related lymphedema (BCRL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Complex decongestive physical therapy is the gold standard for treating lymphedema [5]. Complex decongestive physical therapy includes manual lymphatic drainage therapy, skincare, therapeutic exercises, and compression [5].…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Complex decongestive physical therapy is the gold standard for treating lymphedema [5]. Complex decongestive physical therapy includes manual lymphatic drainage therapy, skincare, therapeutic exercises, and compression [5].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Complex decongestive physical therapy is the gold standard for treating lymphedema [5]. Complex decongestive physical therapy includes manual lymphatic drainage therapy, skincare, therapeutic exercises, and compression [5]. The Faculty of Health Sciences at Bezmialem Vakif University examined the effectiveness of complex decongestive physical therapy for breast cancer surgery patients with reduced range of motion and diminished strength [5].…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…4 Lymphedema is a chronic, progressive, and debilitating complication and one of the most common side effects of breast cancer treatment, which results from the fluid accumulation in the interstitial tissue due to damage to the lymphatic system following surgery, radiography, or tumor. [12][13][14][15] Breast cancer-related lymphedema (BCRL) symptoms impose high costs on patients and increase their distress, reduce the quality of life (QOL), and lead to disability. 16 More than one-fifth of women who survive breast cancer develop lymphedema after breast cancer treatment, affecting more than 40% of the three million breast cancer survivors in the United States.…”
Section: Background and Significancementioning
confidence: 99%
“…A meta-analysis of 12 randomized clinical trials showed that MLD does not significantly reduce or prevent lymphedema in patients with BCRL [8,9]. In terms of treatment, a combination of therapies have been used for decades and involves manual lymphatic drainage, exercises, compression mechanisms and hygienic care [10,11]. In recent years, Godoy & Godoy developed novel concepts and techniques for the treatment of lymphedema, proposing clinical normalization or near normalization even in cases of elephantiasis [12].…”
Section: Introductionmentioning
confidence: 99%